2012
DOI: 10.5334/ijic.797
|View full text |Cite
|
Sign up to set email alerts
|

Integrated transitional care: patient, informal caregiver and health care provider perspectives on care transitions for older persons with hip fracture

Abstract: IntroductionComplex older adults, such as those with hip fracture, frequently require care from multiple professionals across a variety of settings. Integrated care both between providers and across settings is important to ensure care quality and patient safety. The purpose of this study was to determine the core factors related to poorly integrated care when hip fracture patients transition between care settings.MethodsA qualitative, focused ethnographic approach was used to guide data collection and analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(150 citation statements)
references
References 59 publications
4
146
0
Order By: Relevance
“…Moreover, healthcare policies of early discharge and fewer resources for rehabilitation [39][40][41] could push individuals to assume the role of carer: "I think that the sorrowing part that I see, is that it's just all about money, that's all it seems to be…we probably have one of the best health care systems in the world but it's cracking at the seams and you can see it. If this experience taught me anything it was that our health care system is in jeopardy now" [42 p.7].…”
Section: Ii) Providing Supportmentioning
confidence: 99%
“…Moreover, healthcare policies of early discharge and fewer resources for rehabilitation [39][40][41] could push individuals to assume the role of carer: "I think that the sorrowing part that I see, is that it's just all about money, that's all it seems to be…we probably have one of the best health care systems in the world but it's cracking at the seams and you can see it. If this experience taught me anything it was that our health care system is in jeopardy now" [42 p.7].…”
Section: Ii) Providing Supportmentioning
confidence: 99%
“…Frequently the unexpected role and the number of activities that occurred felt overwhelming. Stress, anxiety, frustration, sadness, confusion and lack of time to balance the new role with their personal-life were common feelings identified by carers (Giosa et al, 2014;Nahm et al, 2010;Toscan et al, 2011). Moreover, carers often described the hospital setting and procedures as uninviting and expressed their discontent with the lack of information they received (Giosa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Clear communication has been identified as a critical factor in collaboration to ensure a positive outcome (Boeckxstaens & de Graff, 2011 ;Metzelthin et al , 2013 ;Park et al, 2014;Toscan et al , 2012). This clarity might be achieved through technological knowledge to facilitate connectivity or the physical space required to meet and to exchange ideas and updates.…”
Section: Professional Challengesmentioning
confidence: 99%
“…The concern was confidentiality assurances and the security of private and personal information. In any case, It is not sufficient to only establish a care plan, as the plan need to be reviewed, monitored, and adapted as situations and circumstances change (Boeckxstaens & de Graaf, 2011;Davey et al, 2005 ;Toscan et al, 2012). Legault et al (2012) found that care plans can be enhanced by prioritizing targeted areas, and assigning tasks to individual health care providers, or to the frail older adult patient themselves.…”
Section: Resourcesmentioning
confidence: 99%
See 1 more Smart Citation